2018
DOI: 10.1039/c8cp03609h
|View full text |Cite
|
Sign up to set email alerts
|

Is the formation of N-heterocyclic carbenes (NHCs) a feasible mechanism for the distillation of imidazolium ionic liquids?

Abstract: We describe the synthesis of two tetrachloroindate ionic liquids used as probes to study the involvement of NHCs (N-heterocyclic carbenes) in the distillation of imidazolium derivatives. Atmospheric-pressure chemical ionization mass spectrometry (APCI-MS), electrospray ionization mass spectrometry (ESI-MS), atmospheric-pressure thermal desorption ion mass spectrometry (APTDI-MS) and laser-induced acoustic desorption (LIAD) were used to depict the possibility of the involvement of NHCs during the distillation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…Accordingly, Diniz et al applied the tagging strategy to study the carbene role in the distillation process, demonstrating that both the cation and anion nature can affect the process. [53] In particular, anions from Lewis acids ([InCl 4 ] À ), that commonly prevent the acid-base reactions responsible for the NHC formation in solution, favoured the distillation of ionic liquids as ion pairs, by preserving the cation-anion interaction. As far as the influence of the cation is concerned, the same authors suggested that a dicationic moiety could react with the [InCl 4 ] À anion, allowing the ionic liquid to distillate as a bidentate NHC complex.…”
Section: Esi-ms Detection and Characterization Of Charge-tagged N-hetmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, Diniz et al applied the tagging strategy to study the carbene role in the distillation process, demonstrating that both the cation and anion nature can affect the process. [53] In particular, anions from Lewis acids ([InCl 4 ] À ), that commonly prevent the acid-base reactions responsible for the NHC formation in solution, favoured the distillation of ionic liquids as ion pairs, by preserving the cation-anion interaction. As far as the influence of the cation is concerned, the same authors suggested that a dicationic moiety could react with the [InCl 4 ] À anion, allowing the ionic liquid to distillate as a bidentate NHC complex.…”
Section: Esi-ms Detection and Characterization Of Charge-tagged N-hetmentioning
confidence: 99%
“…As far as the influence of the cation is concerned, the same authors suggested that a dicationic moiety could react with the [InCl 4 ] À anion, allowing the ionic liquid to distillate as a bidentate NHC complex. [53] Turning to the negative ion mode, Lalli et al succeeded for the first time in 2012 in the isolation of N-heterocyclic carbenes bearing negative charge tags. [54] In this case, deprotonation of imidazolium parent cation does not occur through the intervention of the basic counter anion, as in the positive ion mode, but by adding an excess of a strong base (KOtBu).…”
Section: Esi-ms Detection and Characterization Of Charge-tagged N-hetmentioning
confidence: 99%
“…This reaction is a typical deprotonation of the C2-H group of the [EMIM] + cation by a basic counter-ion leading to the spontaneous formation of NHCs, as observed previously. [28][29][30][31][32] Therefore, the products of dissociation of [EMIM][OAc] IL on the glass surfaces are N-heterocyclic carbene (NHC) and acetic acid.…”
Section: N-heterocyclic Carbene Formation Mechanismmentioning
confidence: 99%
“…The possibility of deprotonation of the C2-H group of the [EMIM] + cation by means of a basic counter-ion is known to spontaneously lead to the formation of N-heterocyclic carbene (NHC). [28][29][30][31][32] It has been suggested that the distillation process of [EMIM][OAc] is driven by the formation of NHCs. 28 Both theoretical 32 and spectroscopic 29,30 studies of carbene formation in the gas phase have been presented.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation